Reduced level of physical activity during COVID-19 pandemic is associated with depression and anxiety levels: an internet-based survey - Paulo José Puccinelli; Taline Santos da Costa; Aldo Seffrin; Claudio Andre Barbosa de Lira; Rodrigo Luiz Vancini; Pantelis T. Nikolaidis; Beat Knechtle; Thomas Rosemann; Lee Hill; Marilia Santos Andrade (BMC, 2021)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic has resulted in a strong negative impact on economic and social life worldwide. It has also negatively influenced people's general health and quality of life. The aim of the present study was to study the impact of social distancing on physical activity level, and the association between mood state (depression and anxiety level) or sex with actual physical activity levels, the change in physical activity caused by social distancing period, the adhesion level to social distancing, the adoption time of social distancing, family income and age. Methods A self-administered questionnaire with personal, quarantine, physical activity, and mood state disorders information's was answered by 2140 Brazilians of both sex who were recruited through online advertising. Results The physical activity level adopted during the period of social distancing (3.5 ± 0.8) was lower than that the adopted prior to the pandemic period (2.9 ± 1.1, p < 0.001). Thirty percent of the participants presented symptoms of moderate/severe depression and 23.3% displayed moderate/severe anxiety symptoms. A greater presence of symptoms related to anxiety and depression were associated with low physical activity levels, low family monthly income, and younger age. A higher percentage of men who had no mood disorders was observed among those who were very active than among those less active. Conclusion The COVID-19 pandemic has a negative impact on physical activity. Those who reduced their level of physical activity had the highest levels of mood disorders. Therefore, physical activity programs should be encouraged, while respecting the necessary social distancing to prevent the spread of Severe Acute Respiratory Syndrome Coronavirus 2.